Price sensitivity versus perceived quality: moderating effects of retailer positioning on private label consumption - González-Benito, Óscar; Martos-Partal, Mercedes (Journal of Business Economics and Management, 2014)
Private labels are growing fast in Europe and USA, especially in the context of nondurable consumer goods. Moreover, the traditional association of private labels solely with a price focus, to the detriment of quality, appears to be diminishing. This research aims to clarify the effect of price sensitivity toward and quality perceptions of private labels on private label consumption. It analyzes the role of a retailer’s price positioning as a moderator of the importance of these effects as determinants of private label purchases. With household panel data and survey information, this study investigates private labels’ share of wallet as the dependent variable; thus the logit-type model is adapted to a resource allocation context. Five sequential models specify and test the four hypotheses. In support of the hypotheses, price sensitivity and quality perceptions relate positively to private label consumption. For the moderating effect of retailer’s price positioning, a negative moderating effect arises for price sensitivity, whereas a positive moderating effect appears for quality perceptions of private labels. The findings indicate that retailers’ efforts to convert private labels into tools to support positioning strategies are effective.